Enhancing Digital Communication for Social Inclusion: Tackling English Language Proficiency Gaps in Indonesia (Universitas Terbuka, 2025)
Indonesia’s struggle with English proficiency is holding back its ability to compete globally and connect with the world. This study dives into the current state of English skills in Indonesia, exploring how digital tools—like mobile apps, AI-powered platforms, gamified learning, and even virtual reality—could help turn things around. It also looks at government efforts to bring digital solutions into education. The findings show that better English skills could bring real economic boosts, and things like AI and partnerships between businesses and schools are full of potential. But there’s a catch: challenges like the digital divide, spotty infrastructure, and a lack of trained teachers make it tough to roll these solutions out effectively. While tech offers exciting possibilities, leaning too heavily on it could sideline traditional teaching methods that still work well for learning languages. To make lasting progress, Indonesia needs to ensure everyone has access to these tools, invest in better infrastructure, and find a balance between cutting-edge tech and tried-and-true teaching methods that fits the country’s unique context.